Development of a Web-Based Student Registration System Using Laravel Framework - Faikatul Himmah; Mohamed Salah Laouar (JOKI: Jurnal Komputasi dan Informatika, 2025)
The manual student registration process at TPQ Madinah Baitis Salam Foundation caused administrative inefficiencies, including paper accumulation, delayed data processing, and increased risk of data entry errors. These limitations reduced service quality and hindered effective data management. This study aimed to develop a web-based student registration system to digitalize and streamline the admission process. The system was developed using the Laravel framework with a structured and iterative development approach. Data were collected through direct observation and interviews to identify functional and operational requirements. The system integrates online registration, user authentication, student data management, payment verification, and administrative reporting within a centralized database platform. Functional testing using black-box methods confirmed that all features operated according to system requirements. In addition, a User Satisfaction Test was conducted to evaluate system usability and performance, resulting in an overall satisfaction rate of 90%, categorized as very satisfied. The findings indicate that the developed system effectively improves administrative efficiency, enhances data accuracy, reduces paper-based processes, and increases accessibility for users. The system provides a scalable digital solution suitable for non-formal educational institutions seeking to modernize their admission management processes.